Effect Of Rheological Behaviour Of Cellulose Acetate Spinning Solutions On Performance Of Reverse Osmosis Hollow Fiber Membranes - Idris, Ani; Ismail, A.F.; Gordeyev, S.A.; Shilton, S.J. (Penerbit UTM Press, 2002)
Rheological assessment of cellulose acetate spinning solution using a rotational rheometer and an optical shear cell is carried out so as to study the cause and effect relationship between membrane preparation, polymer morphology and membrane performance. The power law bahaviour, normal force and flow profiles generated provided clues regarding phase inversion and molecular orientation. These rheological results are then related to the separation performance of cellulose acetate reverse osmosis (RO) hollow fibers membranes; both the rejection rate and the flux rate increased with increasing dope extrusion rate, possibly due to molecular orientation.